2015
DOI: 10.1017/ice.2014.77
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection after Renal Transplantation

Abstract: Objective To identify factors associated with the development of surgical site infection among adult patients undergoing renal transplantation. Design A retrospective cohort study Setting An urban tertiary care center in Baltimore, MD with a well-established renal transplantation program that performs approximately 200–250 renal transplant procedures annually. Results 441 adult patients underwent renal transplantation from January 1st, 2010 and December 31st, 2011. Fifteen percent (66/441) of cohort pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 25 publications
(35 reference statements)
2
26
0
5
Order By: Relevance
“…In this study and in prior studies, the positive and negative predictive values of the fields in the electronic medical record/central data repository were greater than 99%. 10-13 …”
Section: Methodsmentioning
confidence: 99%
“…In this study and in prior studies, the positive and negative predictive values of the fields in the electronic medical record/central data repository were greater than 99%. 10-13 …”
Section: Methodsmentioning
confidence: 99%
“…9 Data contained within the tables of this repository have been validated for this and other research studies and were found to have positive and negative predictive values >99%. 1012 In addition, a random sample of 2% of records had all data elements validated and the accuracy of the data was 100% for this dataset.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, wound infections are responsible for longer hospitalizations, increased costs for antibiotic therapy and topical wound care during the same admission and after discharge. In addition, patients who develop wound complications have decreased functional capacity and rely on the assistance of family members or other providers who need to take time off work to drive patients to their frequent clinic appointments [22]. More importantly, in obese renal transplant recipients, surgical site infections (SSIs) have been associated with lower graft survival [15].…”
Section: The Economic and Clinical Burden Of Wound Infectionsmentioning
confidence: 99%